Ultrasonographic examination of the canine skin: a review - MANTIS (Π. ΜΑΝΤΗΣ) P.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Real time B-mode ultrasonography is a non-invasive diagnostic imaging modality that does not use radiation and allows examination of various soft tissue structures. For many years it is used in human dermatology and in the last decade it has entered the canine dermatology arena. Based on the frequency employed, cutaneous ultrasonography may be classified as intermediate- (7-15 MHz) or high-frequency (20 MHz or higher). Using intermediate frequency, the ultrasonographic features of normal canine skin are consistent and three distinct visible layers can be seen. Using a 50 MHz transducer, the epidermis and hair follicles are also identified and accurate measurements of skin thickness can be obtained. The aim of this article is to review the available published knowledge regarding ultrasonographic examination of the canine skin.